2022
DOI: 10.1136/neurintsurg-2022-018780
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cerebral aneurysm occlusion after embolization with the WEB device: a single-institution series of 215 cases with angiographic follow-up

Abstract: BackgroundWoven EndoBridge (WEB) devices are becoming a reliable option for the treatment of wide-neck bifurcation aneurysms, but clear predictive factors are still missing to understand the one in five aneurysm remnant rate.ObjectiveTo evaluate occlusion outcomes after WEB treatment to identify potential determinants of aneurysm occlusion.MethodsA single-center database with consecutive aneurysms treated with WEB between July 2012 and October 2021 was reviewed for potential determinants of aneurysm adequate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In a smaller population but with 5 years of follow-up, Pierot et al 10 described an 11.7% retreatment rate with no observed difference dependent on aneurysm location, and with most procedures performed during the first 2 years post-treatment. In accordance with this, Cortese et al 5 demonstrated that recurrences mostly occur within the 17 months post-implantation, with a stable angiographic result after mid-term control.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In a smaller population but with 5 years of follow-up, Pierot et al 10 described an 11.7% retreatment rate with no observed difference dependent on aneurysm location, and with most procedures performed during the first 2 years post-treatment. In accordance with this, Cortese et al 5 demonstrated that recurrences mostly occur within the 17 months post-implantation, with a stable angiographic result after mid-term control.…”
Section: Discussionmentioning
confidence: 56%
“…The retreatment rate was significantly higher in the ruptured versus the unruptured group (13% vs 3.9%, respectively, P<0.0001). However, since multiple analysis5 18–20 found no statistical association between recurrence and ruptured aneurysm, we can hypothesize that operators were more prompt to treat initially ruptured recurrences, assuming a higher re-rupture risk. Similar observations have been made concerning aneurysms initially treated with coils in some series 15…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, it is recommended to oversize the WEB's width to obtain better occlusion rates. 16,18 It seemed relevant to check if this strategy could be responsible for the TEE, using an "oversizing ratio" to quantitatively evaluate the WEB constraint inside the aneurysm, as previously described. 18 FIGURE 1.…”
Section: Imaging Analysismentioning
confidence: 99%
“…With continuous progress in endovascular treatment technology and concept, as well as rapid development in new materials and equipment, endovascular treatment technology has been widely used in the treatment of intracranial aneurysms. Compared with surgical clipping, interventional embolization of aneurysms has the advantages of less trauma, faster recovery, and lower surgical risk, and has been accepted by the majority of patients as one of the first choices for the treatment of intracranial aneurysms (25,(27)(28)(29)(30)(31). However, the recurrence rate was significantly higher than that of surgical clipping (2, 19-21), with the recurrent ruptured hemorrhage of embolized aneurysms characterized by high mortality and disability, requiring repeated endovascular embolization.…”
Section: Major Findingsmentioning
confidence: 99%